Enhancing diabetic wound healing: advances in electrospun scaffolds from pathogenesis to therapeutic applications - Jiang, Xuewen; Zeng, Yu-E; Li, Chaofei; Wang, Ke; Yu, Deng-Guang (Frontiers in Bioengineering and Biotechnology, 2024)
Diabetic wounds are a significant subset of chronic wounds characterized by elevated levels of inflammatory cytokines, matrix metalloproteinases (MMPs), and reactive oxygen species (ROS). They are also associated with impaired angiogenesis, persistent infection, and a high likelihood of hospitalization, leading to a substantial economic burden for patients. In severe cases, amputation or even mortality may occur. Diabetic foot ulcers (DFUs) are a common complication of diabetes, with up to 25% of diabetic patients being at risk of developing foot ulcers over their lifetime, and more than 70% ultimately requiring amputation. Electrospun scaffolds exhibit a structural similarity to the extracellular matrix (ECM), promoting the adhesion, growth, and migration of fibroblasts, thereby facilitating the formation of new skin tissue at the wound site. The composition and size of electrospun scaffolds can be easily adjusted, enabling controlled drug release through fiber structure modifications. The porous nature of these scaffolds facilitates gas exchange and the absorption of wound exudate. Furthermore, the fiber surface can be readily modified to impart specific functionalities, making electrospinning nanofiber scaffolds highly promising for the treatment of diabetic wounds. This article provides a concise overview of the healing process in normal wounds and the pathological mechanisms underlying diabetic wounds, including complications such as diabetic foot ulcers. It also explores the advantages of electrospinning nanofiber scaffolds in diabetic wound treatment. Additionally, it summarizes findings from various studies on the use of different types of nanofiber scaffolds for diabetic wounds and reviews methods of drug loading onto nanofiber scaffolds. These advancements broaden the horizon for effectively treating diabetic wounds.